Epidemiologia e controle dos principais endoparasitos de cães e gatos domiciliados no município de Alegre-ES - Campos, Diefrey Ribeiro (2014)
The major intestinal endoparasitoses found in pets are mostly zoonosesof importance to public health. The objective of this study was to determine the prevalence and risk factors for the development of gastrointestinal parasites in dogs and cats in the cityof Alegre-ESand determine the effecacyof the treatment of dogs and cats, with different associations of anthelminticon adults of Ancylostomaspp., and Toxocara cati. For the epidemiological study of the experiment 345 dogs and 160 cats domiciled, irrespective of race, sex or age were used. Faecal samples from animals and owners subjected to an interview about handling the animals were collected to determine the risk factors. For the identification of parasites techniques Willis-Molley, simple flotation and sedimentation in formalin-ether were performed. For efficacytesting positive animals were selected for Ancylostomaspp. with 36 dogs divided into three groups containing 12 animals positive for Ancylostomaspp. The cats were divided into 2 groups of 12 animals positive for Ancylostomaspp. and 10 positive for T. cati. totaling 22 cats stool samples from all animals were collected and made the modified McMaster technique for determining the number of eggs per gram of feces (EPG) before treatment and seven days after treatment to determine the percentage of reduction ofOPGand determine the effecacyof the anthelmintic. Data were tabulated and analyzed by chi-square test (p < 0.05) and the calculation of odds ratio with a confidence interval of 95%, to determine the association between the variables of the questionnairewith the results of stool examinations. All statistical analyzes were performed BioEstat software version 5.3. The prevalence of Ancylostomaspp. was 59% to 54% for dogs and cats. The supply of filteredwater, not supply of raw foods, standardization of defecation site, collecting the feces reduce the chances of developing intestinal parasites. The frequency of worming also shown to be a protective factor being that animals in which the anthelmintic is supplied more than once per year have less predisposition to development of intestinal parasitism. Among the active principles used by the owners association of pyrantel pamoate, praziquantel pamoate and febantel was most frequently used by dog owners, while the combination of pyrantel pamoate and praziquantel was the most used by the owners of cats. The effectiveness obtained was 100% for T. catiand 99.6 % for Ancylostomaspp. in cats, dogs while the efficacy was 100 % for the praziquantel and pyrantel pamoate, 99.3% for the association of pyrantel pamoate, praziquantel and febantel and 98.2 % for the control milbemycin oxime Ancylostomaspp